2018
DOI: 10.1523/jneurosci.0801-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Memory-Related Synaptic Plasticity Is Sexually Dimorphic in Rodent Hippocampus

Abstract: Men are generally superior to women in remembering spatial relationships, whereas the reverse holds for semantic information, but the neurobiological bases for these differences are not understood. Here we describe striking sexual dimorphism in synaptic mechanisms of memory encoding in hippocampal field CA1, a region critical for spatial learning. Studies of acute hippocampal slices from adult rats and mice show that for excitatory Schaffer-commissural projections, the memory-related long-term potentiation (LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
129
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(137 citation statements)
references
References 99 publications
8
129
0
Order By: Relevance
“…In humans, neurological disorders such as autismspectrum disorders tend to preferentially affect males rather than females, possibly due to combinatorial contributions of hormonal and genetic factors in a phenomenon known as the female protective effect [78][79][80] , and this is regularly supported with mouse models [81][82][83] . The presence of estrogen and estrogen receptor in the female brain has been shown to be neuroprotective and leads to enhanced Schaffer-collateral LTP 84 . In addition, certain X-linked genes involved in chromatin regulation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, neurological disorders such as autismspectrum disorders tend to preferentially affect males rather than females, possibly due to combinatorial contributions of hormonal and genetic factors in a phenomenon known as the female protective effect [78][79][80] , and this is regularly supported with mouse models [81][82][83] . The presence of estrogen and estrogen receptor in the female brain has been shown to be neuroprotective and leads to enhanced Schaffer-collateral LTP 84 . In addition, certain X-linked genes involved in chromatin regulation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that differences between male and female rats in evoked AMPAR/NMDAR signaling in hippocampal synapses, along with differences in the magnitude of evoked LTP, may underlie sex differences in spatial memory (Monfort et al, 2015;Qi et al, 2016). Estrous has been shown to modulate diffusion of AMPARs to the surface in female mice (Palomero-Gallagher et al, 2003;Tada et al, 2015;Bechard et al, 2018), which may underlie part of the reported importance of estrogenic mechanisms for memory in females (Cordeira et al, 2018;Frick et al, 2018;Koss et al, 2018;Wang et al, 2018;Koebele et al, 2019). However, the sex-specific role of AMPARs in memory may also be specific to the type of memory task being tested, as a study by Dachtler et al concluded that the GluA1 subunit was necessary only for male, not female, mice in fear conditioning memory, but that hippocampal GluA1 was necessary for spatial learning in both sexes (Dachtler et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The normal initiation of SC-LTP in females and the immediate effects of antagonist application on LTP stabilization suggest that the effects rely on local synaptic changes as opposed to ER-driven changes in gene expression at the nucleus. To confirm this, Wang et al (2018) used hippocampal slices taken from NOER (nuclear-only ER1) and MOER (membraneonly ER␣) mutant mice, which lack membrane-associated or nuclear ER␣, respectively (Pedram et al, 2013(Pedram et al, , 2014. As predicted, in slices taken from female NOER mice, LTP failed to stabilize, whereas LTP was unaffected in female MOER mice.…”
mentioning
confidence: 83%
“…To investigate these possibilities, Wang et al (2018) first sought to identify the receptor subtypes that mediate E2 effects on SC-LTP. Application of ER␣-selective antagonist during theta burst stimulation (TBS) in acute brain slices permitted initial potentiation but impaired stabilization of SC-LTP in female, but not in male…”
mentioning
confidence: 99%
See 1 more Smart Citation